Remdesivir versus standard-of-care for severe Coronavirus disease 2019 Infection: an analysis of 28-day mortality - Olender, Susan A. (2022)
Background: Remdesivir is approved by the US Food and Drug Administration for the treatment of patients hospitalized with coronavirus disease 2019 (COVID-19) and has been shown to shorten time to recovery and improve clinical outcomes in randomized trials.